NAC25 transcription factor regulates the degeneration of cytoplasmic membrane integrity and starch biosynthesis in rice endosperm through interacting with MADS29 - Li, Rong; Wu, Ming-Wei; Liu, Jinxin; Xu, Xintong; Bao, Yiqun; Liu, Chun-Ming (Frontiers in Plant Science, 2025)
IntroductionGrain filling is a crucial stage of the rice endosperm development. During this process, the endosperm accumulates abundant storage products such as starch and proteins, which determine both the yield and quality of the grain.MethodsHere, we analyzed the expression of NAC25 transcription factor via qRT-PCR and histochemical GUS assays, and obtained its mutants by CRISPR/Cas9-based gene editing in ZH11.Results and discussionThe results showed that NAC25 was expressed specifically in developing rice endosperm, and knockout of NAC25 led to delayed degeneration of cytoplasmic membrane integrity, reduced starch accumulation and chalky starchy endosperm. We showed that NAC25 interacted with MADS29, a MADS family transcription factor whose mutant also showed defective grain filling. These results provide novel insight into the transcriptional regulation of rice grain filling.